N-Glycosylation Network Construction and Analysis to Modify Glycans on the Spike (S) Glycoprotein of SARS-CoV-2 - Krishnan, Sridevi; Krishnan, Giri P. (Frontiers in Bioinformatics, 2021)
Background: The N-glycan structure and composition of the spike S-protein of SARS-CoV-2 are pertinent to vaccine development and efficacy. Methods: We reconstructed the glycosylation network based on previously published mass spectrometry data using GNAT, a glycosylation network analysis tool. Our compilation of the network tool had 26 glycosyltransferase and glucosidase enzymes and could infer the pathway of glycosylation machinery based on glycans in the virus spike protein. Once the glycan biosynthesis pathway was generated, we simulated the effect of blocking specific enzymes - Swainsonine or Deoxynojirimycn for blocking Mannosidase-II and Indolizidine for blocking alpha-1,6-fucosyltransferase. to see how they would affect the biosynthesis network and the glycans that were synthesized. Results: The N-glycan biosynthesis network of SARS-CoV-2 spike protein shows an elaborate enzymatic pathway with several intermediate glycans, along with the ones identified by mass spectrometric studies. Of the 26 enzymes, the following were involved - Man-Ia, MGAT1, MGAT2, MGAT4, MGAT5, B3GalT, B4GalT, Man II, SiaT, ST3GalI, ST3GalVI, and FucT8. Blocking specific enzymes resulted in a substantially modified glycan profile of the SARS-CoV-2. Conclusions: Variations in the final N-glycan profile of the virus, given its site-specific microheterogeneity, are factors in the host response to the infection, vaccines, and antibodies. Heterogeneity in the N-glycan profile of the spike S protein, and its potential effect on vaccine efficacy or adverse reactions to the vaccines remain unexplored. Here we provide all the resources we generated - the glycans in glycoCT xml format and the biosynthesis network for future work.